Konsep Mutu Penjaminan dan Mutu Pelayanan Pendidikan Islam - Mustika Adriana (Yayasan Rahmat Islamiyah, 2021)
This journal aims to provide an explanation of the concept of quality assurance and service quality in the field of education. Educational institutions must be able to carry out quality mechanisms properly so that these institutions can provide quality as expected and always strive to improve the quality that has been achieved. Quality is determined by two factors, namely the fulfillment of predetermined specifications and the fulfillment of the expected specifications in accordance with the needs and needs of previous customers. Among them are quality in reality and quality in perception.